Strategi Guru PAUD dalam Menerapkan Program 7 Kebiasaan Anak Indonesia Hebat untuk Membentuk Karakter Anak Usia Dini di TK Kristen IV Betania Palangka Raya - Riri Anggraini; Erta Marni Miranti; Susilawati Susilawati; Nita Yuliana; Hartani Hartani (Indo Publishing, 2026)
This study aims to analyze the strategies used by early childhood education teachers in implementing the 7 Habits of Great Indonesian Children Program to develop character in young children at TK Kristen IV Betania Palangka Raya. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving teachers and the principal as research informants. The findings revealed that teachers implemented the program through several strategies, including habituation, role modeling, learning through play, and positive reinforcement. The program was integrated into daily activities such as praying, exercising, practicing healthy eating habits, reading activities, social interaction, and maintaining regular sleep routines. These strategies contributed to the development of positive character traits, including discipline, responsibility, independence, religiosity, healthy living habits, and social awareness among children. Supporting factors included teachers’ commitment, a conducive school environment, and parental involvement. However, the implementation was hindered by the inconsistency of character habituation at home and limited parental participation. The study concludes that the successful implementation of the 7 Habits of Great Indonesian Children Program requires strong collaboration between schools and families to ensure consistent character development in early childhood.